(untitled) (Journal of Kidney Cancer, 2020)
Tuberous sclerosis complex (TSC) is a genetic condition caused by a mutation in either the TSC1 or TSC2 gene. Disruption of either of these genes leads to impaired production of hamartin or tuberin proteins, leading to the manifestation of skin lesions, tumors, and seizures. TSC can manifest in multiple organ systems with the cutaneous and renal systems being the most commonly affected. These manifestations can secondarily lead to the development of hypertension, chronic kidney disease, and neurocognitive declines. The renal pathologies most commonly seen in TSC are angiomyolipoma, renal cysts, and less commonly, oncocytomas. In this review, we highlight the current understanding on the renal manifestations of TSC along with current diagnosis and treatment guidelines.